The Effectiveness of Acceptance and Commitment Therapy on Psychological Symptoms and Dysfunctional Attitudes in Maladjusted Couples Referred to Counseling and Psychological Services Centers - Sanaei Moghadam , Fatemeh; Mohammadzadeh Saraei , Fatemeh Zahra; Arab , Mobina; Ahmadi portesiyeh, Parastoo; Esmaeili Esfandani, Mahsa (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to investigate the effectiveness of Acceptance and Commitment Therapy (ACT) on psychological symptoms and dysfunctional attitudes among maladjusted couples referred to counseling and psychological services centers. The present study employed a quasi-experimental design with a pretest-posttest control group. The statistical population consisted of maladjusted couples referred to counseling centers in Tehran in 2026. A total of 32 participants were selected through convenience sampling and randomly assigned to an experimental group (n = 16) and a control group (n = 16). Data were collected using the Depression, Anxiety, and Stress Scale (DASS-21) developed by Lovibond and Lovibond and the Dysfunctional Attitudes Questionnaire developed by Weissman and Beck. The experimental group received Acceptance and Commitment Therapy over 8 weeks in the form of weekly 90-minute sessions, while the control group received no intervention. Data were analyzed using descriptive statistics and analysis of covariance (ANCOVA) in IBM SPSS Statistics version 27. The results of covariance analysis demonstrated that, after controlling for pretest scores, Acceptance and Commitment Therapy had a statistically significant effect on psychological symptoms among maladjusted couples (F = 21.678, p < 0.001, η² = 0.512). The findings also indicated that ACT significantly reduced dysfunctional attitudes in the experimental group compared to the control group (F = 26.378, p < 0.001, η² = 0.522). The posttest mean scores of psychological symptoms and dysfunctional attitudes in the experimental group were significantly lower than the corresponding pretest scores, whereas no significant changes were observed in the control group. The findings of the present study suggest that Acceptance and Commitment Therapy is an effective intervention for reducing psychological symptoms and dysfunctional attitudes among maladjusted couples.